Development of autonomous cruise control system for convoy vehicle / Daniel Sim Yeat Han, Foong Chee Hin and Hudyjaya Siswoyo Jo - Sim, Daniel Yeat Han; Foong, Chee Hin; Siswoyo Jo, Hudyjaya (UiTM Press, 2015)
This paper presents the tracking and navigation techniques to enable an autonomous vehicle to navigate itself by following the car driving in front of it. The autonomous driving is achieved by tracking and following the leading vehicle based on the visual information acquired by a camera. The position and distance of the leading vehicle are extracted from the characteristics of the unique marker attached at the back of the leading vehicle. Based on the position and distance information, the vehicle will navigate itself to achieve the desired maneuver and distance with respect to the leading vehicle. The visual tracking algorithm is implemented using image acquisition and image processing toolboxes in MATLAB and the navigation algorithm is designed using model-based design approach using SIMULINK.